Pharyngomalacia in Neonates: The Missed Issue - Moslehi, Mohammad Ashkan (Frontiers in Pediatrics, 2020)
Background: Airway malacia (AM) is a weakness of the airway's frameworks making them collapsible during the respiratory phases. Although the larynx, trachea, and bronchus are the usual sites for malacia to occur, there is another important type of malacia that involves the pharynx. Pharyngomalacia (PM) or concentric pharyngeal wall inspiratory collapse (PWIC) is mostly missed during bronchoscopic evaluations in the neonates with noisy breathing because people are not aware of this condition. Methods: This study aimed to evaluate the nasopharyngeal investigation among neonates suffering from noisy breathing. The retrospective study was undertaken to assess the frequency of PM and to propose indications for intervention in 100 neonates with noisy breathing. A thin fiberoptic bronchoscope was used to evaluate the upper airways under conscious status without any sedation in the neonates. Results: A total of 100 neonates with noisy breathing from September 2015 to October 2018 were retrospectively analyzed. The most common presenting symptom was inspiratory stridor which was observed in 35 (92.1%) of cases. PM was diagnosed in 38 neonates (38%) including 27 (71%) males and 13 (29%) females. Seventeen (44.7%) cases had mild, 11 (28.9%) cases had moderate, and 10 (26.4%) cases had a severe type of PM. PM was more prominent at the velopharynx level in 15 (39.4%) cases, and it was accompanied by up to six synchronous airway abnormalities. The most frequent synchronous airway abnormality was laryngomalacia in 13 (34.3%). Conclusion: PM is one of the causes of noisy breathing in infants. Since PM can be accompanied by the presence of other types of airway malacia, the issue becomes more complicated. On the other hand, lack of experience and facilities are two main causes for the accurate diagnosis and effective management among neonates. This study indicates that the investigation of pharynx is a missed part of the many workups that are used to diagnose the site of involvement in neonates with noisy breathing.